Matemática
KatiaMJ
10

(-3ax) / 4 - (-1ax) / 3 + (-1ax) / 2 3a² - [2a -1- (2a² -5a + 3)] -6 a- { -b + [ ( a-c) - ( -b + c) ] - 4a }

+1
(1) Respostas
gabrielvb

(-3ax) / 4 - (-1ax) / 3 + (-1ax) / 2   - 3ax  + 1ax - 1ax           mmc = 12       4          3      2    -9ax + 4ax - 6ax             12       - 11ax          12 ================================================ 3a² - [2a -1- (2a² -5a + 3)] -6 3a² - [2a -1- 2a² + 5a - 3] -6 3a² - [ - 2a² + 7a - 4 ] - 6 3a² + 2a²  - 7a + 4  - 6 5a²  - 7a  - 2 ================================================= a- { -b + [ ( a-c) - ( -b + c) ] - 4a } a- { -b + [  a - c + b - c ] - 4a } a- { -b + [  a  + b - 2c ] - 4a } a- { -b +  a  + b - 2c - 4a } a- { - 3a  - 2c } a + 3a  + 2c  4a + 2c

Adicionar resposta